2010
DOI: 10.1089/hum.2009.143
|View full text |Cite
|
Sign up to set email alerts
|

Interference of CD40L-Mediated Tumor Immunotherapy by Oncolytic Vesicular Stomatitis Virus

Abstract: Oncolytic virotherapy can be achieved in two ways: (1) by exploiting an innate ability of certain viruses to selectively replicate in tumor tissues, and (2) by using viruses to deliver toxic or immunostimulatory genes to tumors. Vesicular stomatitis virus (VSV) selectively replicates in tumors lacking adequate type I interferon response. The efficacy of oncolytic virotherapy using VSV against B16 melanomas in C57BL=6 mice is dependent on CD8 þ T and natural killer cells. Because immunotherapies that prime spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 30 publications
6
68
0
1
Order By: Relevance
“…For several reasons, however, this approach has proven more challenging, including the facts that (1) real self-tumor antigens are relatively weak as the host is tolerized towards them and contains very few T-cell precursors (39); (2) the selective pressure applied by immune therapies towards a single tumor antigen can lead to escape variants (44), and (3) OVs are extremely immunogenic themselves and may distract the immune system from the tumor (34,45). To address aspects of these barriers, two innovative approaches have recently been developed.…”
Section: Engineering Oncolytic Vaccines To Prime or Boost Antitumor Imentioning
confidence: 99%
“…For several reasons, however, this approach has proven more challenging, including the facts that (1) real self-tumor antigens are relatively weak as the host is tolerized towards them and contains very few T-cell precursors (39); (2) the selective pressure applied by immune therapies towards a single tumor antigen can lead to escape variants (44), and (3) OVs are extremely immunogenic themselves and may distract the immune system from the tumor (34,45). To address aspects of these barriers, two innovative approaches have recently been developed.…”
Section: Engineering Oncolytic Vaccines To Prime or Boost Antitumor Imentioning
confidence: 99%
“…Early studies demonstrated the presence of tumor-specific CD8 T cells following VSV treatment and a reduction of the therapeutic effect after CD8 T cell depletion (15). However, subsequent studies indicated that tumor-specific CD8 T cells either were not detected in the tumor, spleen, or draining lymph nodes following VSV treatment (35) or were detected at low levels that were not statistically significant (9,10,17,37). It was also suggested that tumor regression in CD8 T cell depletion experiments was the result of nonspecific CD8 T cell activation induced by VSV rather than a tumor-specific response (17, 35).…”
mentioning
confidence: 99%
“…Transgenes have been added to oncolytic VSV vectors in an attempt to improve on efficacy through modulation of the immune response, with varying impacts on therapeutic outcome. 9,[31][32][33][34] A number of groups have added cytokines, including IL-4, IL-12 and IL-23, into VSV in an effort to polarize the adaptive immune response to improve on anti-tumor immune responses. Although there was some improvement over parental control viruses, the immune responses were either not measured in these studies or showed no, or only very minor, increases to immune responses, leaving room for further improvement.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Alternatively, co-stimulatory molecules have been expressed from the OV VSV vector again with no improvement over control viruses in survival or induction of immune responses. 9 To improve on the oncolytic efficacy of VSV, we have added a highly secreted form of human IL-15 to our oncolytic VSV vector for its immuno-stimulatory effects on innate and acquired immunity. 12,15,16,35 The addition of the hIL-15 transgene did not impair viral replication in vitro and led to high levels of secretion of hIL-15 from virally infected cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation